Peran Keuangan Syariah dalam Mendorong Pertumbuhan Ekonomi Nasional - Rinda Trihariyanto, Ranto (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
Islamic finance is a financial system based on Islamic principles that emphasize justice, transparency, and the prohibition of interest (riba), uncertainty (gharar), and gambling (maisir). Over the past two decades, Islamic finance in Indonesia has experienced rapid growth both in terms of institutions and financial instruments. This study aims to analyze the role of Islamic finance in promoting national economic growth through intermediation, financing the real sector, and strengthening financial inclusion. The research method used is a literature review by analyzing reports from the Financial Services Authority (OJK), Bank Indonesia, and academic publications. The results show that Islamic finance contributes to increasing financial inclusion, strengthening financial system stability, and supporting productive sector financing. The study emphasizes the importance of product innovation, financial literacy, and regulatory support to expand the role of Islamic finance in Indonesia.